ANALYSIS OF THE INFLUENCE OF SALES RETAIL MIX ON CONSUMER SATISFACTION AT THE VIVA PET SHOP OF SUKOHARJO - Putri Purnamasari, Eva; Sumarto, Laksono; Zailani, Abdullah (IJBLE Scientific Publications Community Inc., 2023)
Managing Viva Pet Shop in Sukoharjo Regency realizes that the business provides equipment and everything related to pets, it's very similar to a business that supplies children and toddlers. The emotions of the customer are key there, so sometimes the prices are not so major consideration. Available products, quality of service, the building, the location, and also to determine consumer satisfaction pet shop. So in the purchase of the product for a beloved pet, the consumer will have a lot of consideration to determine the pet shop that he would visit to buy the needs of the pet. The purpose of this study is to determine whether there is an influence on retail sales mi to the satisfaction of the consumer at the Pet Shop Sukoharjo. This research is quantitative descriptive using descriptive statistical analysis, the classical assumption, multiple linear regression, and hypothesis testing. Data collection using a questionnaire with a Likert scale of 5 points. The results of this study stated that there is an influence in retail sales mi to the satisfaction of the consumer at the Pet Shop Sukoharjo.